Optimalisasi Kesejahteraan Psikologis Mahasiswa Perantauan Melalui Konseling Komunitas Berbasis Self-Determination - Ramjani Novita Fajar Ningrum; Nazilatur Rahmadani; Widya Hayuningtyas Rahma Kusumawardhani; Rizki Nurfauziah; Universitas Negeri Semarang (CV. Ulil Albab Corp, 2024)
Overseas students tend to study far from their place of residence. This makes students not in the environment of the closest people such as family, closest relatives, friends and friends at home. Living overseas is not easy to adjust to the new environment. Students who cannot adjust overseas tend to feel sad because they need to adjust to the culture in their new environment. This will certainly have an impact on the psychological well-being of overseas students, because not all of them are able to face these demands. Not a few of them feel lonely and alone. This research was conducted to find out how to optimize the psychological well-being of overseas students with self-determination-based community counseling. This research uses the literature review method which is carried out by finding several sources related to variables. The results showed that Self-Determination-based community counseling proved to have several effective efforts to support the psychological well-being of overseas students. The Self-Determination counseling approach model focuses on fulfilling three needs, namely competence, autonomy and connectedness. Implementation of Self-Determination-based community counseling includes identification of needs, formation of support groups, social activities, social skills training, autonomy facilities, mentoring, evaluation and feedback.